Devolatilization Studies of Oil Palm Biomass for Torrefaction Process through Scanning Electron Microscopy - Daud D.; Rahman A.A.; Shamsuddin A.H. (Institute of Physics Publishing, 2023)
Biomass; Electron microscopy; Palm oil; Renewable energy resources; Biomass structure; Devolatilization; Empty fruit bunches; Morphology structures; Oil palm biomass; Palm kernel shells; Palm oil biomass; Scanning electron microscopy image; Scanning electron microscopy; biochemical composition; correlation; essential oil; evergreen tree; experimental design; fruit; morphology; phytomass; residence time; scanning electron microscopy; temperature effect; Elaeis